Manejo da adubação na cultura do feijão em sistema de produção orgânico - Pereira, Leandro Barradas [UNESP]; Arf, Orivaldo [UNESP]; dos Santos, Neli Cristina Belmiro; de Oliveira, Aline Estela Zini; Komuro, Lauro Kenji (My University, 2015)
Nowadays the food production systems tend to include the sustainable management of soil and water. One of the main obstacles to the organic cultivation of common bean is the fertilization management. This study aimed to evaluate doses of organic fertilizer containing slaughterhouse residues (1.0 t ha−1, 1.5 t ha−1, 2.0 t ha−1 and 2.5 t ha−1). The experimental design was randomized blocks in a 4x2x2 factorial scheme, with 16 treatments and 4 replications. Plant dry weight; foliar diagnose; initial and final plant population; number of pods per plant, grains per plant and grains per pod; 1000-grain weight; and grain yield were evaluated. It was concluded that the methods and time of organic fertilizer application do not affect the production components and yield in common bean. The dose of 2.5 t ha−1 of organic fertilizer provided the highest common bean yield in 2012, but it did not express its maximum production capacity.
Fertilization management in bean crop under organic production system
Keywords: Cattle residues; Organic fertilizer; Phaseolus vulgaris L.